Profiling Peminjam Berdasarkan Demografi dan Karakteristik Kredit Menggunakan Metode Clustering: Studi pada Koperasi Serba Usaha KSU Bintang Muda 88 - Olivia Oktevi Alexander; Marinus Ronal; Marchelin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to ensure that the credit provided is truly safe, so as to expedite the process of granting credit, and prevent bad credit. The data collection procedure in this research is through documentation and literature. Based on data analysis carried out by researchers using the clustering method, it can be concluded that the customer groups analyzed show different characteristics and require adapted strategies from cooperatives.